Customs modernization initiatives : case studies - Wulf, Luc de; Sokol, José B. (Washington, DC : World Bank, 2004)
A companion to the 'Customs Modernization Handbook', this book provides case studies on customs modernization initiatives in seven countries: Bolivia, Morocco, Mozambique, Peru, the Philippines, Turkey, and Uganda. The initiatives in each of these countries show similarities as well as differences in their approach and design. Some have relied on a model of independent revenue authorities (Uganda and Peru), others have called upon private sector service providers to initiate the modernization process (Mozambique), others have taken the drastic step of a complete overhaul of their customs staff (Bolivia and Mozambique), others introduced new information technology to streamline customs processes and to integrate other members of the trading community into an electronic network (Ghana), while still others have approached the modernization process as a pragmatic, well-focused, result-oriented process.
Includes bibliographical references and index.
rpm 25/08/16
Loans
Keywords: Customs administration; Customs administration - Developing Countries; MEDICAL--Public Health